A NEW FRAMEWORK: FACTORS DETERMINING STUDENTS' INTENTIONS TO PURSUE HIGHER EDUCATION-STRUCTURAL, CULTURAL, AND SCHOOL STRATEGIES - Fajar Agung Pangestu; Hilda Rakerda (Pascasarjana Unviersitas Majalengka, 2026)
The declining interest of high school students in continuing their education to college is a global concern, reflecting the gap in educational access and learning motivation. This study aims to develop a new framework to understand the factors influencing students' interest in further study. A mixed method approach was used, with quantitative data from 97 students via questionnaires and qualitative data from in-depth interviews with three teachers and six students in three schools. The results indicate that students' decisions are influenced by an integration of structural factors (economic conditions and parental support), cultural factors (local social and cultural environment), and the strategic role of schools. Economic factors and parental approval are the main determinants, while peer influence and local culture shape personal motivation. School strategies have a role to play in intervening in these structural and cultural barriers.